Effects of Preoperative Non-Steroidal Anti-Inflammatory Drugs on Pain Mitigation and Patients' Shoulder Performance Following Rotator Cuff Repair - Alireza Rouhani; Ali Tabrizi; Asghar Elmi; Naghi Abedini; Fardin Mirza Tolouei (Tabriz University of Medical Sciences, 2014)
Purpose: Pain is one of the most important factors adversely affecting clinical outcomes of operated patients. The present study aims at evaluating effects of preoperative COX2 non-steroidal anti-inflammatory inhibitors on pain mitigation and performance of patients with shoulder rotator cuff tear. Methods: This case-control study was conducted on 60 patients suffering from rotator cuff injury candidate for arthroscopic repair. The patients were classified in two parallel and matched groups. One group (case group) was treated using Celecoxib (200mg/12h) started 48 hours before surgery and continued for 10 days after operation. In the control group, the placebo was prescribed in the same way. Postoperative pain, side effects, sleep disturbance, and short-term outcomes were compared between two groups using DASH questionnaire. Results: Postoperative pain in the Celecoxib group significantly decreased in comparison with the control one. The difference was statistically meaningful (P<0.001). Well motion ability was seen in 80% of patients of the Celecoxib group. It was 26.6% in the placebo group since pain inhibited them from exercising more motions. In this regard, there was a statistically meaningful difference between these two groups (P=0.02). Sleep disturbance was meaningfully at higher levels in the placebo group (P=0.001). Following up the patients for three months, it was made clear that performance of the Celecoxib group was better than that of the placebo one. Conclusion: COX2 inhibitors are well efficient in patients' pain management after arthroscopic rotator cuff repair surgery. It results in less life complications, less sleep disturbances, improvement of patients' short-term clinical outcome, and more quick recovery.